ON SOME ECOLOGICAL AND BIOLOGICAL FEATURES OF TULIPA BIEBERSHTEINIANA ROEM. ET SCHULT. IN THE TERSKOY UPLAND CONDITIONS OF REPUBLIC OF INGUSHETIA - L. S. Khashieva; M. K. Dakieva; M. M. Buzurtanova (Юг России: экология, развитие)
Aim. The aim of the research is to study the ecological and biological features and evaluation of the current state of coenopopulations of Tulipa biebershteiniana Roem. et Schult. in the Terskoy upland conditions of Republic of Ingushetia (RI), a valuable ornamental species decreasing in number.Methods and materials. T. Biebershteiniana species have been chosen and collected within RI as the material for ecological and biological research. Collection of herbarium material and recording observations, ecological and phenological characteristics of the species have been carried out during two growing seasons (2014-2015) using conventional methods.Result. We have found that on the territory of Ingushetia population of the species Tulipa biebershteiniana Roem. et Schult. can be found only in the area of the Terek ridge on the slopes of the north-western and south-eastern exposures in the vicinity of the rural settlement of Voznesenskaya and Yuzhnoye, in the bushes in a dry clay soils at an altitude of 500-600 meters above sea level sporadically. On the basis of ecological and biological study of features of T.biebershteiniana in terms of its natural habitat we describe ontogenesis and full morphogenesis of its monocarpic shoots. We have also detected the factors limiting its coenopopulations. The growing places of T.biebershteiniana species have been identified, thus we have carried out mapping of its range on the territory of Ingushetia. The soil texture has been studied from natural places of T.biebershteiniana.Conclusion. The research on population status of T. Biebersteiniana on the territory of the Republic of Ingushetia has showed a low density and a limited range of its distribution, and therefore we have made recommendations on taking protective measures of natural spaces of its growth and of making it into the Red Book of the Republic of Ingushetia as a category of III rarity status.